Emerging Roles of T Cells in the Pathogenesis of Nonalcoholic Steatohepatitis and Hepatocellular Carcinoma - Hirsova, Petra; Bamidele, Adebowale O.; Wang, Haiguang; Povero, Davide; Revelo, Xavier S. (Frontiers in Endocrinology, 2021)
Nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease worldwide. A significant proportion of patients with NAFLD develop a progressive inflammatory condition termed nonalcoholic steatohepatitis (NASH), which may eventually advance to cirrhosis and hepatocellular carcinoma (HCC). NASH is characterized by steatosis, hepatocyte ballooning, and lobular inflammation. Heightened immune cell infiltration is a hallmark of NASH, yet the mechanisms whereby hepatic inflammation occurs in NASH and how it contributes to disease initiation and progression remain incompletely understood. Emerging evidence indicates that intrahepatic T cell immune mechanisms play an integral role in the pathogenesis of NASH and its transition to HCC. In this review, we summarize the current knowledge regarding the T cell-mediated mechanisms of inflammation in NASH. We highlight recent preclinical and human studies implicating various subsets of conventional and innate-like T cells in the onset and progression of NASH and HCC. Finally, we discuss the potential therapeutic strategies targeting T cell-mediated responses for the treatment of NASH.